THE EFFECT OF INTERMITTENT FASTING 5:2 ON BODY FAT PERCENTAGE AND THICK UNDER-SKIN FAT FOLDS IN OVERWEIGHT AND OBESE INDIVIDUALS - Esa Indah Ayudia; Miftahurrahmah; Indri Okta Sapitri; Huntari Harahap; Rina Nofri Enis; Hafizah (Fakultas Kedokteran Universitas Sriwijaya, 2025)
Overweight and obesity is a condition in which there is an imbalance between the entry and exit of energy for a long time. Intermittent Fasting is one of the dietary interventions that can affect body composition such as body fat percentage and thick folds of fat under the skin. The purpose of this study was to determine the effect of Intermittent Fasting type 5:2 on body fat percentage and thick folds of fat under the skin in individuals with overweight and obesity. This study is an experimental study using pretest and posttest group design. The number of samples was 50 people with a consecutive sampling method. The statistical test used was the paired t-test. The results showed that intermittent fasting had a significant effect on body fat percentage (p<0.001), thick folds of fat under the skin of the biceps (p=0.009), and triceps (p<0.001), while the supra iliac and subscapular parts decreased but statistically insignificant (p=0.093) and (p=0.217).